Pengaruh Suku Bunga Deposito Terhadap Perkembangan Dana Deposito - Amelia Marbun; Anju Rayman Lumban Gaol; Febtri Basaria Marbun; Rolinda Lumban Gaol; Ruth Marselina Sihombing; Christnova Hasugian; Hamonangan Siallagan (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
Deposits as a financial instrument have become the main choice among the public and business people in the modern economy. providing security and stable profits. The main factor that influences the decision to place funds in deposits is the interest rate offered by financial institutions. This strategic decision requires careful consideration in the dynamics of an economy that continues to develop. This research aims to investigate how deposit interest rates influence people's and companies' decisions in placing their funds, as well as the impact of changes in interest rates on the development of deposit funds. This research will also explore factors that can moderate the influence of deposit interest rates on the development of deposit funds. It is hoped that this research can provide better insight for stakeholders in managing their financial portfolios effectively in the context of dynamic financial markets. The research stage begins with a literature study which includes a literature review on the influence of deposit interest rates on the development of deposit funds. Sample selection was carried out to determine the bank or financial institution that would be the focus of the research. The research variables involve deposit interest rates as the independent variable and the development of deposit funds as the dependent variable. The data collection method is carried out by collecting historical data on deposit interest rates and the development of deposit funds from sources such as central banks, financial institutions, or economic databases. Annual or quarterly financial data from selected banks is the focus of the analysis. The results of the discussion conclude that deposit interest rates influence public and company decisions in placing funds. Competitive interest rates increase the attractiveness of deposits as a safe investment. Company decisions are influenced by liquidity considerations and capital requirements for long-term investments. Changes in interest rates influence the growth or shrinkage of deposit funds, with rising interest rates increasing the attractiveness of deposits.